Airway neutrophilia in stable and bronchiolitis obliterans syndrome patients following lung transplantation. Issue 1 (1st January 2000) - Zheng, Ling; Walters, E Haydn; Ward, Chris; Wang, Ning; Orsida, Bernadette; Whitford, Helen; Williams, Trevor J; Kotsimbos, Tom; Snell, Gregory I
Abstract : BACKGROUND: The bronchiolitis obliterans syndrome (BOS) remains the major constraint on the long term success of lung transplantation. Neutrophils have been associated with fibrosing lung conditions and have been noted to be increased in the bronchoalveolar lavage (BAL) fluid of patients with BOS. METHODS: This study was undertaken to examine neutrophil accumulation in the BAL fluid, airway wall and lung parenchyma, as well as levels of interleukin (IL)-8 in the BAL fluid, in normal controls and lung transplant recipients with and without BOS. Bronchoscopic examination included endobronchial biopsy (EBB), BAL fluid, and transbronchial biopsy (TBB) sampling. Tissue neutrophils were identified by neutrophil elastase staining on 3 μm paraffin biopsy sections and quantified by computerised image analyser. IL-8 levels were measured in unconcentrated BAL fluid by ELISA. RESULTS: Compared with controls, airway wall neutrophilia was increased in both stable lung transplant recipients and those with BOS (p<0.05). BAL neutrophils and IL-8 levels were also increased in both groups of transplant recipients compared with controls (p<0.01), the levels being significantly higher in the BOS group (p<0.01). Neutrophil numbers in the lung parenchyma were not significantly different between the two groups of lung transplant recipients. CONCLUSION: Increased levels of neutrophils are present in the airway wall and BAL fluid of lung transplant recipients with and without BOS. BAL fluid levels of IL-8 are also increased, raising the possibility that neutrophils and/or IL-8 may play a part in the pathogenesis of BOS following lung transplantation.